Factors Influencing Students’ Speaking Passivity on Social Media - Khamalia, Novi Aghata Nur; Imaniar, Fahmy (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Speaking is one of the essential skills that every individual, especially students, must possess to support their other abilities. In this highly modern era, social media needs to be explored, particularly concerning students' speaking skills. Many students remain passive when speaking through social media. This case is intriguing to explore and investigate. This research aims to investigate the factors that can influence students' speaking passivity on social media, using a qualitative approach. Data were obtained by interviewing the English subject teachers of the 10th grade in a private high school in Surabaya. The researcher found that several factors influencing the speaking passivity of 10th-grade students include fear of making mistakes, bad pronounciation, and a lack of vocabulary. The results of this research can serve as a reference for both students and teachers to study solutions for these factors.